An Efficient Total Synthesis of (–)‐(R), (+)‐(S)‐Lavandulol Pheromones and Their Derivatives through Proline Catalyzed Asymmetric α‐Aminooxylation and [3, 3] Claisen Rearrangement. Issue 3 (30th January 2017) - Bhosale, Viraj A.; Waghmode, Suresh B.
Abstract: An efficient total synthesis of the enantiomerically pure lavandulol pheromones viz . (–)‐( R ) and (+)‐( S )‐lavandulol, (–)‐( R )‐lavandulyl acetate, (–)‐( R )‐lavandulyl propionate, (+)‐( S )‐lavandulyl 2‐methylbutanoate and (+)‐( S )‐lavandulyl senecioate is accomplished from nonchiral and chiral materials. The strategy utilizes a sequence of proline catalyzed asymmetric α‐aminooxylation and [3, 3] Claisen rearrangement for stereodivergent synthesis of chiral C‐2 unit containing 4‐pentenols. Abstract : Lavandulol pheromones and their derivatives have been efficiently synthesized from chiral C‐2 unit containing 4‐pentenol, which was accessed by using proline catalysed α‐aminooxylation and [3, 3] sigmatropic Claisen rearrangement of allyl vinyl ether as the key steps.